Cactaceae at Caryophyllales.org – a dynamic online species-level taxonomic backbone for the family - Korotkova, Nadja; Aquino, David; Arias, Salvador; Eggli, Urs; Franck, Alan; Gómez-Hinostrosa, Carlos; Guerrero, Pablo C; Hernández, Héctor M; Kohlbecker, Andreas; Köhler, Matias; Luther, Katja; Majure, Lucas C; et al. (Willdenowia, 2021)
This data paper presents a largely phylogeny-based online taxonomic backbone for the Cactaceae compiled from literature and online sources using the tools of the EDIT Platform for Cybertaxonomy. The data will form a contribution of the Caryophyllales Network for the World Flora Online and serve as the base for further integration of research results from the systematic research community. The final aim is to treat all effectively published scientific names in the family. The checklist includes 150 accepted genera, 1851 accepted species, 91 hybrids, 746 infraspecific taxa (458 heterotypic, 288 with autonyms), 17,932 synonyms of accepted taxa, 16 definitely excluded names, 389 names of uncertain application, 672 unresolved names and 454 names belonging to (probably artificial) named hybrids, totalling 22,275 names. The process of compiling this database is described and further editorial rules for the compilation of the taxonomic backbone for the Caryophyllales Network are proposed. A checklist depicting the current state of the taxonomic backbone is provided as supplemental material. All results are also available online on the website of the Caryophyllales Network and will be constantly updated and expanded in the future. Citation: Korotkova N., Aquino D., Arias S., Eggli U., Franck A., Gómez-Hinostrosa C., Guerrero P. C., Hernández H. M., Kohlbecker A., Köhler M., Luther K., Majure L. C., Müller A., Metzing D., Nyffeler R., Sánchez D., Schlumpberger B. & Berendsohn W. G. 2021: Cactaceae at Caryophyllales.org – a dynamic online species-level taxonomic backbone for the family. – Willdenowia 51: 251–270. Version of record first published online on 31 August 2021 ahead of inclusion in August 2021 issue. Data published through: http://caryophyllales.org/cactaceae/Checklist